Рroblems using protyoblidnyuvalnyh liquids in ukraine - Бойченко, С.В.; Іванова, Г.В.; Кумейко, О.В. (Proceedings of National Aviation University, 2006)
The condition of use anti-icing’s liquid of liquids is considered during operation of flying devices in Ukraine. The basic operational parameters anti-icing’s liquid of liquids are classified. The special attention is given to detailed study of the different marks anti-icing’s liquid of liquids with the description of their basic properties and technology of use.